1995
DOI: 10.1902/jop.1995.66.7.579
|View full text |Cite|
|
Sign up to set email alerts
|

Immunohistochemical Expression of Extracellular Matrix Components of Normal and Healing Periodontal Tissues in the Beagle Dog

Abstract: Periodontal regeneration requires formation of periodontal tissues lost due to periodontal disease. To better understand the formation of new periodontal tissues during periodontal repair and regeneration, immunohistochemical expression of extracellular matrix components of normal as well as healing periodontal tissues was evaluated and compared using the avidin-biotin complex immunohistochemical technique. For this purpose, horizontal furcation defects were created around mandibular P2 and P4 of 6 dogs after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
53
1
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 44 publications
9
53
1
6
Order By: Relevance
“…After 14 days, the tissue can present new collagen fibers, with an organization indicative of attachment to the dentin. Describing the tissues formed at 2 weeks of wound healing after GTR, Matsuura et al (21) reported that the defect was occupied predominantly by granulation tissue composed of numerous inflammatory cells and blood vessels, as well as formation of a fine layer of connective tissue between the granulation tissue and the root surface. At this stage, there is no significant bone or cementum formation.…”
Section: Discussionmentioning
confidence: 99%
“…After 14 days, the tissue can present new collagen fibers, with an organization indicative of attachment to the dentin. Describing the tissues formed at 2 weeks of wound healing after GTR, Matsuura et al (21) reported that the defect was occupied predominantly by granulation tissue composed of numerous inflammatory cells and blood vessels, as well as formation of a fine layer of connective tissue between the granulation tissue and the root surface. At this stage, there is no significant bone or cementum formation.…”
Section: Discussionmentioning
confidence: 99%
“…The periodontal ECM is rich in collagen, fibronectin, tenascin, periostin, and other matrix molecules. 4,5 Collagen I is the principal protein component of Sharpey's fibers 6 and periostin is an indicator molecule of a functional PDL, as its expression changes dynamically in response to tension and compression. 7 Other periodontal glycoproteins such as fibronectin and tenascin provide arginin-glycine-aspartic acid (RGD) motifs for cell adhesion.…”
mentioning
confidence: 99%
“…Various surgical procedures have been developed for healing class II or III furcation defects (4,6), and various bone grafts and alloplastic materials have been transplanted (5,24,29); however, ankylosis, resorption, and long epithelial attachment are observed in alloplastic material-applied cases (8). It has been demonstrated that GTR is capable of successfully closing class III furcation defects in a dog model (11,17,18); however, the regeneration of class III furcation defects is often incomplete, even when GTR is employed, suggesting that this treatment is not effective for large, class III furcation defects (15,21,22), as it depends on natural healing ability. Since pPDL is basically capable of synthesizing periodontal tissue after transplantation, this treatment may be applicable to large periodontal tissue defects.…”
mentioning
confidence: 99%